PERILAKU KONSUMSI MINUMAN ALKOHOL DAN PERILAKU AGRESIF MAHASISWA RANTAU ASAL X DI SALATIGA - Venessya Manuhutu; Christiana) Hari Soetjiningsih (Jurnal Inovasi Penelitian, 2022)
The quantitative research aims to determine the relationship between alcohol consumption behavior and aggressive behavior in Students from X who study in Salatiga. The research instrument using The alcohol use disorders identification test (AUDIT) and “The Aggression Questionnaire” which have met requirements of good reliability. The data collection technique used was a purposive sampling technique with 44 participants. The results showed there was significant positive relationship between alcohol consumption behavior and aggressive behavior, which means that the higher the behavior of alcohol consumption, the higher the aggressive behavior, and vice versa. A total of 17 students (38,6%) were in zone IV (problematic) in alcohol consumption behavior. This result can be used as a basis for efforts to prevent the consumption of alcoholic beverages.